2008
DOI: 10.1111/j.1537-2995.2007.01604.x
|View full text |Cite
|
Sign up to set email alerts
|

Basic science focus on blood substitutes: a summary of the NHLBI Division of Blood Diseases and Resources Working Group Workshop, March 1, 2006

Abstract: In March 2006, a workshop sponsored by the National Heart, Lung, and Blood Institute was convened to identify the role of basic science research in clarifying issues that are impeding progress in the development of hemoglobin-based oxygen carrying (HBOC) solutions. These discussions resulted in a consensus that, although HBOCs have shown clinical promise, various side effects have inhibited further development and regulatory approval, with cardiovascular events being of particular concern. As a consequence, wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 16 publications
0
35
0
Order By: Relevance
“…These detrimental properties of the TrpE7 and TrpE11 mutations probably account for the unsuccessful initial human safety trials of rHb2.0 that was based on the rHb3011 design. The oxidative stress and inflammation resulting from plasma Hb denaturation seem a likely cause of complement activation, although this conclusion needs further testing (40). Regardless, it is clear that alternative strategies are needed for lowering NO scavenging while retaining low rates of autooxidation, hemin loss, and globin unfolding.…”
Section: Autooxidation Hemin Loss and Reactivity With H 2 Omentioning
confidence: 99%
See 3 more Smart Citations
“…These detrimental properties of the TrpE7 and TrpE11 mutations probably account for the unsuccessful initial human safety trials of rHb2.0 that was based on the rHb3011 design. The oxidative stress and inflammation resulting from plasma Hb denaturation seem a likely cause of complement activation, although this conclusion needs further testing (40). Regardless, it is clear that alternative strategies are needed for lowering NO scavenging while retaining low rates of autooxidation, hemin loss, and globin unfolding.…”
Section: Autooxidation Hemin Loss and Reactivity With H 2 Omentioning
confidence: 99%
“…The rHb3011 molecule has also been shown to reduce or prevent gastrointestinal dysmotility (54), and its genetic background was built into the last Baxter HBOC prototype, rHb2.0, which also showed no hypertensive side effect (56,84,110,116,142,155). However, rHb2.0 was later shown to cause complement activation in initial safety trials in humans (40), which, as shown in Figure 5, appears to be due to high rates of autooxidation, hemin loss, and/or globin denaturation, properties that were not optimized in the second-generation product, but have been shown to lead to endothelial damage and inflammatory responses (8-10).…”
Section: Controlling O 2 Affinity and Nodmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, essential paradigms regarding oxygen delivery (e.g., impact of low oxygen affinity and low viscosity) have recently been challenged by the innovative design of Hemospan™, indicating that a better understanding of oxygen delivery at the site of microcirculation and oxygenation of tissues, cellular, and subcellular structures may be required for an appropriate efficacy-assessment of OCBS. To this end, most target parameters may predominantly be assessed in experimental models, and these experiments should be predictive of response in humans, incorporate stress conditions, and be used to systematically evaluate the effect of variation of Hb structure, biochemistry, and physical chemical properties [23].…”
Section: Expert Opinionmentioning
confidence: 99%